Taking the Lead: New Roles for University Teachers - Galina Gushcha (International Society of Philosophy and Cosmology, 2015)
The article is devoted to the role and the place of University teaching staff in educational process ofinstitutions of higher learning.The key concepts of pedagogical activities are defined.The research highlights the teacher's creativityregardingeducational efficiency